Zonasi Harga Lahan Permukiman Kota Pontianak Dengan Memanfaatkan Citra Ikonos = Zoning The Price of Residential Land of Pontianak City by using the Ikonos Image - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT The main constraint of collecting data on the factors determinent the price of settlement land of a region is the tedious fieldwork absorbing plenty mandays. Ikonos image may help to minimize the constraint in this respect. This research is aimed to study the spatial distribution of the price of the settlement land in the study area using Ikonos image and its zonation as well. Scoring and weighting method is adopted in this study. Scoring is applied to the parameter affectial the price of the settlement land in the district of Pontianak city, whereas weighting is based on the influence of each parameter to the price of the land. Frequency analysis and spatial analysis are used in this study. The result of the study indicates that the interpretation accuracy on the land use based on Ikons image is 94,20%. High price of the settlement land associates with dense block of settlement, positive land accessibility is high, and good utility. The zonation of the land price in the study area based on Ikonos image interpretation is 88,33% in accordance to the legal land zonation price issued by the Service of Building and Land Tax.